Assessment of neck circumference in a sample of primary school children - Mohd Yusof, Barakatun Nisak; Ismail, Intan Hakimah; Amin Nordin, Syafinaz; S., Nurul Ain (Community Health Society Malaysia, 2018)
Background: Neck circumference (NC) is one of the proposed assessments for child obesity, but limited information is available for Malaysian children. This study assessed NC and its relationship with anthropometric indices in a sample of primary school children. Materials and Methods: This cross-sectional study recruited 758 children aged 7-10 years old from a selected primary school in Serdang, Selangor. Anthropometric indices included assessments of height, weight, waist circumference (WC) and NC. Body mass index (BMI) was calculated which was then used to determine BMI-for-age Z-score based on the WHO Child Growth Standard.